2014
DOI: 10.1111/imj.12343
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous thrombolysis is unsafe in stroke due to infective endocarditis

Abstract: Embolic stroke is the most common neurological complication of infective endocarditis and a major source of morbidity and mortality. Septic embolism is considered a contraindication to intravenous thrombolysis in patients with ischaemic stroke because of concerns over an increased risk of intracranial haemorrhage. We describe a patient with occult endocarditis who was treated with thrombolysis for acute stroke and review other cases reported in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…In the milieu of septic embolisation, IV-tPA has been reported to be associated with increased risk of bleeding and poor lytic efficacyhence increased probability of poor angiographic and clinical outcomes. 5,16 Consistent with the predominance of RBCs interspersed within fibrin bands in our retrieved clots, we found prominent early imaging signs such as the hyperdense middle cerebral artery (HDMCA) sign on NCCT in all four cases. Other studies have also reported a correlation between these early imaging signs with the density of RBCs in the retrieved thrombi of non-IE-related cases.…”
Section: Discussionsupporting
confidence: 81%
“…In the milieu of septic embolisation, IV-tPA has been reported to be associated with increased risk of bleeding and poor lytic efficacyhence increased probability of poor angiographic and clinical outcomes. 5,16 Consistent with the predominance of RBCs interspersed within fibrin bands in our retrieved clots, we found prominent early imaging signs such as the hyperdense middle cerebral artery (HDMCA) sign on NCCT in all four cases. Other studies have also reported a correlation between these early imaging signs with the density of RBCs in the retrieved thrombi of non-IE-related cases.…”
Section: Discussionsupporting
confidence: 81%
“…There are concerns about the safety and efficacy of IV‐tPA in the setting of septic emboli . Known endocarditis is a contraindication to IV‐tPA primarily due to concerns about bleeding risk .…”
Section: Discussionmentioning
confidence: 78%
“…Moreover, few cases occurred symptomatic intracranial hemorrhages [3]. On the other hand intravenous tissue plasminogen activator is high risk of the complication of intracerebral hemorrhage [3][4][5][6]. Anotheris the pathology of the retrieved thrombus leads to definitive diagnosis for embolic stroke of unknown origin [7].…”
Section: Discussionmentioning
confidence: 99%